Analisis Penerapan Ekonomi Sirkular dan Inovasi Hijau UMKM: Studi Kasus Kabupaten Pesawaran - Farhani, Armachika; Fitri, Annisa; Sormin, Rahma Diani (Universitas Multi Data Palembang, 2025)
The transition to a sustainable economy requires the integration of green innovation and circular economy principles. This study explores how independent entrepreneurs and micro, small, and medium enterprises (MSMEs) leverage sustainable practices to achieve long-term economic growth. Using a qualitative case study-based approach, this study involved 7 MSMEs in Pesawaran Regency who have implemented circular economy principles through textile waste recycling, eco-friendly accessory production, and innovation using used raw materials. Data were collected through in-depth interviews, participant observation, and document analysis and validated using source and method triangulation. The results showed that the implementation of a circular economy increased cost efficiency by 30% and increased business competitiveness by up to 45% compared to conventional business models. However, the main challenges in the form of minimal recycled raw materials, lack of technology, and the absence of supporting policies are still the main obstacles. Therefore, collaboration between entrepreneurs, the government, and the green business community is needed to accelerate the implementation of a circular economy in Indonesia.